1979
DOI: 10.1093/oxfordjournals.aje.a112660
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Nineteen-Year-Old Men: Family Size and Birth Order Associations

Abstract: The authors analyzed the prevalence of obesity by family size and birth order for a total population of over 280,000 19-year-old Dutch males, who were born between 1944 and 1947 and who were from one- to five-child families. Obesity was defined by a relative weight index, 120% or more of the standard of weight for height. Overall obesity prevalence was 1.83%; sons of manual workers were more prone to obesity than sons of non-manual workers. Individuals from one-child families (only children) were uniquely at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 0 publications
4
29
3
Order By: Relevance
“…Although some previous studies did not found an association between weight status and family composition (47) , Padez et al (7) also found in their cross-sectional study among 7-to 9?5-year-old children that being a single child was significantly associated with overweight in girls. This has also been reported in the past for the UK (48) , the Netherlands (49) and more recently by the IDEFICS Study (Identification and prevention of Dietaryand lifestyle-induced health Effects In Children and infantS) (50) using data of eight European countries. Children without siblings possibly got less PA, had greater sugar consumption and were more likely to have a TV in their bedroom (50) .…”
Section: Discussionsupporting
confidence: 75%
“…Although some previous studies did not found an association between weight status and family composition (47) , Padez et al (7) also found in their cross-sectional study among 7-to 9?5-year-old children that being a single child was significantly associated with overweight in girls. This has also been reported in the past for the UK (48) , the Netherlands (49) and more recently by the IDEFICS Study (Identification and prevention of Dietaryand lifestyle-induced health Effects In Children and infantS) (50) using data of eight European countries. Children without siblings possibly got less PA, had greater sugar consumption and were more likely to have a TV in their bedroom (50) .…”
Section: Discussionsupporting
confidence: 75%
“…The protective influence of sibship size has been reported in the UK (Whitelaw, 1971) and in Holland (Ravelli & Belmont, 1979). According to our study, being a firstborn was the aspect that proved to affect overweight or obese status, as there was no difference in comparison to being a single child.…”
Section: Discussionsupporting
confidence: 67%
“…The inverse relationship between the number of children in the family and overweight found in a number of studies 21,40,41 may also be caused by overprotection of single children. The lack of evidence showing the relationship between this factor and overweight in our study may be a result of the correlations between the different social factors.…”
Section: Discussionmentioning
confidence: 96%